NEUROMANAGEMENT. A MANAGEMENT STRATEGY FOR THE SUCCESS OF AN ORGANIZATION - Chávarro Méndez, Jairo; Piña Ferrer, Lenys (Revista Arbitrada Formación Gerencial, 2022)
Neuromanagement is the application of neuroscience to management and business life. In this case, the objective of this article is to analyze the contributions of neuromanagement as a management strategy for the success of organizations. In turn, the methodology used was the documentary analysis, which was focused on the confrontation of contributions from different authors about neuromanagement. As conclusion, a successful management influences the development of a good organization, where those that incorporate neuroscience have better processes, and then neuromanagement is conceptualized as a management model. This suggests, that with implementation, is expected to have companies and organizations more efficient and more productive, with the best human talent and results, that is, to have organizational succeed, goal of all entrepreneur, and in this context, of all neuromanager.